Using Life of Pi Novel to Promote Character Education in English Class - Anastasia Camelia Wardhani; Ouda Teda Ena (Institut Agama Islam Negeri Palopo, 2020)
The objective of this research is to design English learning material for Junior High School in Indonesia. The material developed is intended as supplementary material to promote character education in English class. The material designed is based on Martel’s Life of Pi novel published in 2001. This novel is about Pi’s strategies to survive in the middle of the ocean and therefore it is suitable to promote character education. The developed material consists of four units. Each unit consists of reading, vocabulary, writing, group work and reflection. The four aspects of character education to learn are appreciate others, respect older people, be grateful and appreciate God’s creatures. Unit I consists of activities and materials to promote appreciation for others. Unit II deals with respecting the elders. Unit III is designed to promote gratefulness. While Unit IV is aimed at appreciation of God’s creatures. Research and Development is used as the method in conducting the study and designing the material. The instruments are including open-ended questionnaire, the themes found in “Life of Pi” Novel and one week observation during the English subject in the class. The developed material has been evaluated and deemed as very good after the revision. The tasks are considered as suitable for Junior High School students, the reading material is appropriate and the layout is interesting. The supplementary material is necessary due to the fact that the textbooks used in the Junior High School do not cover character education.